ISOLATION AND IDENTIFICATION OF ROTAVIRUS FROM NEONATAL CALVES - M. Odisho, Shoney; Albana, Antons.; KH. Majeed, Amjad (The Iraqi Journal of Veterinary Medicine, 1996)
Bovine rotavirus was successfully isolated in vero cell line and secondary calf kidney cell culture from faecal samples of newly bom calves affected with diarrhoea. The isolated viruses were cultivated from cell culture produced cytopathogenic effect which consisted of cytoplasmic granulation degeneration and detachment of infected cells from monolayer cell culture. The rotavirus was identified by indirect immunofluorecent test (IFT) and neutralization test (NT) by using reference hyperimmunser.